PENGARUH PROFITABILITAS, LIKUIDITAS DAN LEVERAGE TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR SEKTOR BARANG KONSUMSI YANG TERDAFTAR DI BEI PERIODE 2020- 2023 - Yulius Iwang; Shadrina Hazmi (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2023)
The purpose of this study was to analyze the effect of profitability, liquidity, and leverage on company value in manufacturing companies in the consumer goods sector which are listed on the IDX for the 2020-2023 period. The sample in this study is Manufacturing Companies Registered on the IDX for the 2020-2022 period, namely www.idx.co.ic. Methods of data collection by searching for financial statements (financial statements), annual reports (annual reports), literature studies and documentation collection. This study uses multicollinearity techniques, t test, f test and coefficient of determination test. The results of this study indicate that there is a significant influence between profitability, liquidity, and leverage on firm value in manufacturing companies in the consumer goods sector listed on the IDX for the 2020-2023 period.